New Normal in Recruitment Market, The Use of Transparency and Warning Message in Non face-to-face Interview: Effects on Applicants' Reactions and Faking - Kim, Jae Cheol; Jeong, Da Jung; Kang, Min Gyun; Jung, Ji Woo; Heo, Chang Goo (Korean Journal of Industrial and Organizational Psychology, 2022)
This study sought to examine the effects of transparency and warning messages on applicants' reactions and faking in non-face-to-face interview situation. A study was performed with a 2(transparency vs. non transparency) x 2(warned vs. unwarned) factorial design, Interviewees(N=82) were randomly assigned to each conditions and participated in non-face-to-face interviews. The main results and meanings of this study are as follows: First, the transparency group perceived higher information known, chance to perform, and procedural justice than non-transparency group during the interview process. Second, transparency did not increase the faking, and significantly reduced the extensive image creation. Third, the warning message reduced the overall level of faking, specifically reducing the use of slight image creation and image protection. Fourth, warning messages increased performance anxiety, but did not have a significant effect on chance to perform and procedural justice recognition. This study provided meaningful implication in that it conducted an empirical study on the applicants' reactions and behavior in non-face-to-face interviews, and it is expected that it will be used as basic explanation for constructing non-face-to-face interviews by suggesting the possibility of using transparency and warning messages.